On the variability of hemispheric scale energy parameters - McGuirk, James P., author; Reiter, Elmar R., author; Barbieri, Ann M., author; Colorado State University, publisher (Colorado State University. Libraries, 1975)
Hemispheric scale energy parameters have been computed and their variability on an annual time scale and a scale of a few weeks is identified and discussed. Based on data for 15 winter seasons, the annual variability of available potential energy is linked to fluctuations of elements of the general circulation, such as the jet streams. This link establishes a relationship between simply computed hemispheric scale parameters and regional weather conditions affecting man's economic wellbeing. Daily statistics on three winter seasons of hemispheric energy modes have been analyzed with the ultimate goal of understanding and reproducing the behavior of the hemispheric energy cycle. Two phenomena are discussed: (1) A strong 22-26 day cycle in the energy modes which may be linked to synoptic scale systems and the atmospheric index cycle; and (2) A large midwinter "dip" in zonal available potential energy which is tentatively linked to a possible movement of the Hadley cell. This "dip" is shown to have a profound effect on the meridional temperature gradient, particularly in midlatitudes.
January 1975.
USAEC Report No. C00-1340-41.
Keywords: Atmospheric circulation; Energy budget (Geophysics)